2019
DOI: 10.1523/jneurosci.0299-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA TLK1 Aggravates Neuronal Injury and Neurological Deficits after Ischemic Stroke via miR-335-3p/TIPARP

Abstract: Circular RNAs (circRNAs) are expressed at high levels in the brain and are involved in various CNS diseases. However, the potential role of circRNAs in ischemic stroke-associated neuronal injury remains largely unknown. Here, we investigated the important functions of circRNA TLK1 (circTLK1) in this process. The levels of circTLK1 were significantly increased in brain tissues in a mouse model of focal cerebral ischemia and reperfusion. Knockdown of circTLK1 significantly decreased infarct volumes, attenuated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(104 citation statements)
references
References 61 publications
5
96
0
3
Order By: Relevance
“…Our results also support previous findings that circRNAs can serve as novel diagnostic biomarkers and promising therapeutic targets for IS 26,[36][37][38][39] . In the present study, based on the results of bioinformatic analyses, three of the top ten significantly DE circRNAs were selected for PCR validation in AIS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results also support previous findings that circRNAs can serve as novel diagnostic biomarkers and promising therapeutic targets for IS 26,[36][37][38][39] . In the present study, based on the results of bioinformatic analyses, three of the top ten significantly DE circRNAs were selected for PCR validation in AIS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Recent research has shown that the expression of circTLK1 was significantly upregulated in animal brains and circulating blood from animal models of IS and IS patients. Furthermore, knockdown of circTLK1 significantly reduced infarct volumes, decreased ischemic neuronal damage, and improved neurological deficits 13 . Another study manifested that the expression of circRNA HECTD1 was associated with risk, severity and recurrence of AIS 14 .…”
mentioning
confidence: 89%
“…As shown in our previous studies, circular RNA SHOC2 (circSHOC2) ameliorates ischemic damage by regulating the autophagy of neurons. 19 In the present study, the circRNA circUCK2 was upregulated during the acute period after focal ischemia. circUCK2 is expressed in neurons, but its function remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was increased in the mouse brain after tMCAO and knocking down circRNA TLK1 improve neurological deficits and infarct volume in this stroke mouse model. Remarkably, circRNA TLK1 was observed to be also elevated in human patients after ischemic stroke [38].…”
Section: Discussionmentioning
confidence: 99%